Immunological Responses and Epitope Mapping by Tuberculosis-Associated Antigens within the RD1 Region in Japanese Patients - Hideaki Nagai; Maho Suzukawa; Yumi Sakakibara; Ken Ohta; Pedro A. Reche; Koichi Suzuki; Yoshihiko Hoshino (Journal of Immunology Research)
Tuberculosis remains a major global health problem worldwide, and hence there is a need for novel vaccines that better induce cellular-mediated immunity (CMI). In search of a better vaccine target, the QuantiFERON-TB Gold In-Tube Test (QFT-GIT) and the interferon-γ ELISPOT assay (ELISPOT) were used to compare the magnitude of CMI in patients. Results of the ELISPOT assay led to the discovery of specific epitopes within the early secreted antigenic target 6 kDa (ESAT-6) and culture filtrate protein 10 kDa (CFP-10) proteins. Both peptides showed a strong association with several HLA class II DRB1 molecules in the Japanese population. Using ESAT-6-specific HLA class II tetramers, we determined that the expression of ESAT-6-specific CD4+ lymphocytes was significantly decreased in treated patients compared with active patients. In addition, programmed death-1 (PD-1)/killer cell lectin-like receptor G1 (KLRG-1) double positive cells were found only in treated patients and not in those with active TB. These data could provide clues for the development of novel tuberculosis vaccines.